2000
DOI: 10.1897/1551-5028(2000)019<2341:pottom>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of the Toxicity of Multiple Chemical Mixtures to Vibrio Fischeri: Mixtures Composed of Similarly Acting Chemicals

Abstract: Abstract-The prediction of combined effects based on the effects of the individual components of mixtures by using the pharmacological concepts of concentration addition and independent action might be a promising tool for the risk assessment of pollutant mixtures. To analyze and compare the predictive capabilities of the reference concepts for similarly acting chemicals, the overall toxicity of a multiple mixture was determined in a bioluminescence inhibition assay with Vibrio fischeri. The mixture was compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
221
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 258 publications
(237 citation statements)
references
References 22 publications
6
221
0
3
Order By: Relevance
“…Conversely, when both cypermethrin and Pb 2þ were causing toxicity, both concentration addition (CA) and independent action (IA) modeling techniques were used. For a binary mixture, the CA and IA models can be expressed using Equations 1 and 2, respectively [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, when both cypermethrin and Pb 2þ were causing toxicity, both concentration addition (CA) and independent action (IA) modeling techniques were used. For a binary mixture, the CA and IA models can be expressed using Equations 1 and 2, respectively [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [17,27,28] have shown that chemicals with differing MOAs tend to be best modeled by IA, and those with similar MOA tend to best be modeled by CA. The IA model better predicted joint toxicity of cypermethrin and Pb 2þ , indicating that MOA for the contaminants may differ.…”
Section: Antagonistic Joint Toxicity Of Cypermethrin and Leadmentioning
confidence: 96%
“…Other authors require that a similar effect is localized at least in the "same site of primary action", while a dissimilar effect is distinguished from this by the criterion of differences in a substances" fundamental structure (different "parent compounds") [37]. However, recent research has shown that mixtures which were designed of components known to act either by identical or by completely different molecular mechanisms of action were in fact better predicted by concentration addition or independent action respectively [7,9,38,39].…”
Section: The Quest For the Right Conceptmentioning
confidence: 99%
“…This strategy also allowed tackling the question of whether effect thresholds of individual mixture components were protective against combination effects. A series of studies was designed to test multi-component mixtures with wellknown mechanisms and modes of action for their components to investigate the following: 1) reference mixtures composed of compounds with entirely similar and dissimilar action [7,8]; 2) mixtures with components in concentrations at and below statistically significant effects [9]; and 3) 2 different biological systems (bacteria and algae) to provide a proof of principle [7,9]. As a prerequisite to meet the goal of analyzing low effect concentrations in the mixture experiments rigorous concentrationresponse estimations were performed employing a so-called "best fit modeling," based on the simultaneous application of different nonlinear concentration-effect regression models [10].…”
mentioning
confidence: 99%
“…See Table S1 for the number of citations and rank of all the "Top 100" papers, which in this essay are references [7,8].…”
mentioning
confidence: 99%